Influence of different scion-rootstock combinations on sugars, polyamines, antioxidants and malondialdehyde in grafted grapevines under arid conditions - Krishankumar, Sonu; Hunter, Jacobus J.; Alyafei, Mohammed; Souka, Usama; Subramaniam, Sreeramanan; Ramlal, Ayyagari; Kurup, Shyam S.; Amiri, Khaled M. A. (Frontiers in Plant Science, 2025)
IntroductionGrapevines are an important and economically significant fruit plant that is cultivated worldwide. Most of the world’s emerging wine-growing regions are in arid or semi-arid regions that are severely affected by drought. Grafting has emerged as an effective strategy to enhance drought tolerance, but the influence of scion–rootstock combinations on key biochemical and antioxidant parameters under water deficit conditions is not fully understood. MethodThe study investigates the effects of grafting on antioxidant enzymes, malondialdehyde (MDA), polyamines and sugar metabolism in five grafted grapevine combinations exposed to three irrigation levels to optimise sustainable grape production in the arid regions of the UAE. Leaf samples were analysed for polyamines, MDA and sugars using liquid chromatography. ResultsThe study found that the drought-tolerant rootstocks Paulsen, R110 and Ramsey increased cell activity, reduced ROS production, lowered MDA levels and increased antioxidant capabilities. SOD activity increased significantly under 75% and 50% FC by 225% in V1, 316% in V3, 133% in V4 and 1025% in V5. In response to severe drought at 75% and 50% FC, V2 and V5 showed a decrease in MDA accumulation (by 34.2% and 50% in V2 and 23.7% and 57.6% in V5, respectively) compared to 100% FC (0.76 nmoL mL−1 in V2 and 1.18 nmoL mL−1 in V5). Polyamines generally showed an increase with decreasing field capacity, indicating drought tolerance. Different polyamine contents were observed in grafted vines. V1, V2 and V5 showed higher levels of spermine and free spermidine, while V3 and V4 were more sensitive to drought stress. Organic osmolytes positively influenced the enzymatic activity in drought-tolerant grafts. Sugars built up in the grafts and had a signalling function as Osmo protective molecules. The shoots improved sugar metabolism, which led to increased resistance to drought. There was a significant increase in glucose sugar content at 75% and 50% FC, which was 85.7% to 133% at V1, 19% to 76.9% at V2, and decreased by 30% and 53% at V4.DiscussionThe results suggest that grafted grapevines have a strong ability to cope with drought stress by upregulating antioxidant enzymes and altering other compounds such as MDA, PA and sugars that are conducive to stress tolerance.